Urea as the Nitrogen source in NIT Hydroponic System - Hussin, Aminuddin; Abdul Raffar, Khalip; K., Norayah; Husin, Alias (Universiti Putra Malaysia Press, 1993)
Urea as the source of nitrogen in the nutrient solution in NIT (nutrient film technique) hydroponic system undergoes hydrolysis which results in the release of ammonium in solution. Urea hydrolysis was rapid from the 7th day onwards and ended by the 20th day. At the same time, ammonium concentration in solution increased and reached its maximum on the 20th day. Nitrification occurred simultaneously and peaked also on the 20th day. Plant dry matter weight at harvest was similar for both urea and nitrate treatments. Ammonium concentration in leaves and roots was higher in urea than in nitrate treatments. Nitrate concentration in leaves and roots was similarfor both treatments. The study showed that urea can be substituted for nitrate as the nitrogen source in the NIT hydroponic system.